"Modern Day Trojan Horse?" Analyzing the Nexus between Islamophobia and Anti-Refugee Sentiment in the United States. Issue 2 (1st October 2020) - Hodson, Margaret
Abstract : Although Islamophobia in the United States has long predated the election of President Donald Trump, the collision of anti-Muslim and anti-refugee sentiments is a relatively new development. This article explores how the Islamophobia industry—notably the Center for Security Policy and ACT for America—has mobilized its anti-Muslim ideologies to dismantle the U.S. Refugee Admissions Programs (USRAP). A review of works by prominent anti-Muslim authors demonstrates how the Islamophobia industry misconstrues migration—or "hijra"—as a national security threat, by linking refugees to "civilization jihad" and terrorism. Consequently, the Islamophobia industry has undermined the traditional bipartisan consensus on refugee resettlement in the United States dating back to World War II. The Trump administration has lent high-level support and impact to these ideologies by enacting the so-called "Muslim Ban" to prevent Muslim refugees from entering the United States. This article traces the history of U.S. refugee resettlement policy and explores the contemporary challenge it faces from rising Islamophobia.